The Determinants of Detrimental Changes in Pulse Pressure During Maintenance Hemodialysis Treatments - Ratna Damayanti; Iri Kuswadi; Raden Heru Prasanto; Metalia Puspitasari; Yulia Wardhani; Danny Pratama Kuswadi (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Background: Studies indicate that large fluctuations in pulse pressure during hemodialysis are associated with cardiovascular events, cardiovascular mortality, and all-cause mortality. Objective: We investigated the determinants of detrimental changes in pulse pressure (ΔPP) during hemodialysis. Methods: This prospective, observational cohort study was conducted from 1 to 30 April 2023 at Dr. Sardjito Hospital Yogyakarta, involving maintenance hemodialysis patients for ≥ 6 months. Patients were categorized into group 1 (detrimental ΔPP, ΔPP >5 mmHg or <−25 mmHg) and group 2 (stable ΔPP, −25 to 5 mmHg). Mann-Whitney, independent-t, chi-square, Fisher exact tests, and logistic regression were applied to evaluate associations between ΔPP groups and clinical variables. Results: This study involved 136 patients, 75 males (55.1%) with a mean age of 52 (18-87). The most common comorbid was hypertension, present in 85 patients (62.5%). The mean hemodialysis vintage of patients was 47.2 (6.5-330.7) months. We found significant difference between group in post-dialysis systolic blood pressure (SBP) (p=0.003), pre-dialysis diastolic blood pressure (DBP) (p=0.015), post-dialysis DBP (p=0.007), ultrafiltration (p=0.041), pre-dialysis mean-arterial-pressure (MAP) (p=0.013), post-dialysis MAP (p=0.002), and alpha-blocker treatment (p=0.037). Multivariate logistic regression analysis shows a significant association between groups of ΔPP with pre-dialysis DBP (p=0.035; OR=1.153; OR=Exp(10xℬ) =4.137) and post-dialysis SBP (p=0.007; OR=1.052; OR=Exp(10xℬ) =1.6487). Conclusion: Our study demonstrates that group 1, with detrimental changes in pulse pressure during hemodialysis, was found to have higher post-dialysis DBP, pre-dialysis DBP, post-dialysis SBP, pre-dialysis MAP, post-dialysis MAP, alpha-blocker treatment, and ultrafiltration, with significant association with post-dialysis SBP and pre-dialysis DBP.